The First Described Case of Occupational Anthracofibrosis in the USA. (23rd December 2014) - Rangelov, Kamen; Sethi, Sanjay
Abstract : Anthracofibrosis is a newly recognized disease that was first described in association with tuberculosis in 1998 in Korea. However, recent reports suggest strong association with biomass fuel smoke exposure, and exposure to mineral dusts, coal, silica, and mica. Most of the reported cases to date are in patients from Asia or in immigrants of Asian origin. There are no published reports of anthracofibrosis in the USA. We present the first case of a USA born African American male patient with anthracofibrosis.